Analisis Perbedaan Penggunaan Metode Pengakuan Pendapatan Margin Murabahah Terhadap Kualitas Laba (Studi Kasus pada Bank Syariah di Indonesia Tahun 2011-2013) - Dwi Wulan Ramadani; Noven Suprayogi (Universitas Airlangga, 2016)
This study aims to determine the presence or absence of differences in the earnings quality on murabaha margin revenue recognition. The sample used in this study selected by purposive sampling method. It produces 6 Islamic Banks (BUS) in Indonesia with the data obtained from their annual reports that have already been published. The research used a quantitative approach using equations of regression to detect the presence or absence of earnings management, which then in different test using independent t-test. The variable in this study is earnings quality that is categorised based on the use of murabaha margin revenue recognition method. Results shows that differences in using murabaha margin revenue recognition method has an impact on quality of earnings. However, the statistical test indicated that there was no significant difference to the quality of earnings.